Targeting Tryptophan Catabolism in Cancer Immunotherapy Era: Challenges and Perspectives - Peyraud, Florent; Guegan, Jean-Philippe; Bodet, Dominique; Cousin, Sophie; Bessede, Alban; Italiano, Antoine (Frontiers in Immunology, 2022)
Metabolism of the essential amino acid tryptophan (Trp) is a key metabolic pathway that both promotes tumor cell intrinsic malignant properties as well as restricts antitumour immunity, thus emerging as a drug development target for cancer immunotherapy. Three cytosolic enzymes, indoleamine 2,3-dioxygenase 1 and 2 (IDO1/2) and tryptophan 2,3-dioxygenase (TDO2), catalyzes the first-rate limiting step of the degradation of Trp to kynurenine (Kyn) and modulates immunity toward immunosuppression mainly through the aryl hydrocarbon receptor (AhR) activation in numerous types of cancer. By restoring antitumor immune responses and synergizing with other immunotherapies, the encouraging preclinical data of IDO1 inhibitors has dramatically failed to translate into clinical success when combined with immune checkpoints inhibitors, reigniting the debate of combinatorial approach. In this review, we i) provide comprehensive evidences on immunomodulatory role of the Trp catabolism metabolites that highlight this pathway as relevant target in immuno-oncology, ii) discuss underwhelming results from clinical trials investigating efficacy of IDO1 inhibitors and underlying mechanisms that might have contributed to this failure, and finally, iii) discuss the current state-of-art surrounding alternative approaches of novel anticancer immunotherapies targeting both the upstream and downstream effector molecules of Trp catabolism as well as challenges and perspectives in the era of immunotherapy.